Cellulose Science and Derivatives - Sand, Arpit; Banga, Sangita (IntechOpen, 2021)
Cellulose and cellulose derivatives are a class of bio-based materials that have attracted scientific interest due to their unique structural features and properties such as biocompatibility, biodegradability, and renewability. They are promising candidates for applications in biomedicine, pharmaceuticals, electronics, barrier films, nanocomposites, membranes, and supercapacitors. New resources, extraction procedures, and treatments are currently under development to satisfy increasing demands for cost-effective and sustainable methods of manufacturing new types of cellulose nanoparticle-based materials on an industrial scale. This book, written by an international collection of contributors in the field, is a useful reference for graduate students and researchers in chemistry, materials science, nanoscience, and green nanotechnology.